Evaluation of electronic prescription implementation in polymedicated users of Catalonia, Spain: a population-based longitudinal study. Issue 11 (5th November 2014) - Lizano-Díez, Irene; Modamio, Pilar; López-Calahorra, Pilar; Lastra, Cecilia F; Segú, Jose L; Gilabert-Perramon, Antoni; Mariño, Eduardo L
Abstract : Objectives: To assess whether electronic prescribing is a comprehensive health management tool that may contribute to rational drug use, particularly in polymedicated patients receiving 16 or more medications in the public healthcare system in the Barcelona Health Region (BHR). Design: 16 months of retrospective study followed by 12 months of prospective monitoring. Setting: Primary healthcare in BHR, Catalonia, Spain. Participants: All insured patients, especially those who are polymedicated in six basic health areas (BHA). Polymedicated patients were those with a consumption of ≥16 drugs/month. Interventions: Monitoring demographic and consumption variables obtained from the records of prescriptions dispensed in pharmacies and charged to the public health system, as well as the resulting drug use indicators. Territorial variables related to implementation of electronic prescribing were also described and were obtained from the institutional data related to the deployment of the project. Main outcome measures: Trend in drug use indicators (number of prescriptions per polymedicated user, total cost per polymedicated user and total cost per prescription) according to e-prescription implementation. Results: There was a significant upward trend in the number of polymedicated users, number of prescriptions and total cost (p<0.05), which seemed independent from the implementation of electronic prescribing when comparing the preimplementation and postimplementation period. Prescriptions per user and cost per user showed a decrease between the preimplementation and postimplementation period, being significant in two BHAs (p<0.05). Conclusions: Results suggest that after the implementation of electronic prescribing, the rationality of prescribing in polymedicated patients improved. In addition, this study provides a very valuable approach for future impact assessment.